Fed up - Soechtig, Stephanie; Marson, Eve; Olson, Sarah (Producer); Monroe, Mark; Couric, Katie, 1957-; Brook, Michael, 1952-; Atlas Films; RADiUS TWC (Firm); Artemis Rising Foundation; Diamond Docs (Firm); Anchor Bay Entertainment, Inc. (2014)
Narrated by Katie Couric, the film blows the lid off everything that was known about food and exercise, revealing a 30-year campaign by the food industry, aided by the U.S. government, to mislead and confuse the American public. Exposing the hidden truths contributing to one of the largest health epidemics in history, it follows a group of families battling to lead healthier lives and reveals why the conventional wisdom of 'exercise and eat right' is not ringing true for millions of people.
"Special features not rated"--Container.
Original score, Michael Brook.
Narrator, Katie Couric.
MPAA rating: PG (some material may not be suitable for children) for thematic elements including smoking images, and brief mild language.
DVD; NTSC; anamorphic widescreen presentation (1.78:1); Dolby Digital 5.1.
English dialogue; English or Spanish subtitles; subtitled for the deaf and hard of hearing.
Keywords: Food industry and trade -- Corrupt practices -- United States; Food industry and trade -- Moral and ethical aspects -- United States; Food industry and trade -- Government policy -- United States; Advertising -- Food -- Moral and ethical aspects -- United States; Nutrition policy -- United States; Nutrition -- United States; Food habits -- United States; Obesity in children -- United States; Obesity -- United States; Exercise; Documentary films; Nonfiction films; Video recordings for the hearing impaired